Sistem Pendukung Keputusan Menentukan Jenis Bibit Padi Terbaik Menggunakan Metode MOORA Berbasis Web (Studi Kasus: Desa Tanen Selo Grobogan) - Sri Rama Putri; Lestiani (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Selection of the type of rice seeds is the most important factor to produce quality rice. Farmers' knowledge and experience is also very important to be able to choose the best type of rice seeds. In Tanen Selo Grobogan Village, there are still many farmers who do not understand and lack experience in determining the best type of rice seeds to plant on their farms. There is no system that can help farmers in Tanen Selo Grobogan Village to determine the best type of rice seeds so that farmers still rely on experience from the previous year's harvest or try new rice seeds without paying attention to the selection of rice seeds. So that the rice produced is not satisfactory. To overcome this problem, a decision support system was created to determine the best type of rice seed using the Multi-Objective Optimization On The Basis Of Ratio Analysis (MOORA) method. The designed system will be implemented in a web-based application created using the PHP programming language and MySQL as the database server. The results of this study will add to the knowledge and experience of farmers in how to determine the best types of rice seeds and make it easier for farmers in Tanen Selo Village to determine the best types of rice seeds to be planted on their agricultural land quickly and precisely.